THE ORIGIN OF THE UZBEK LITERARY LANGUAGE AND ITS HISTORICAL DEVELOPMENT ON THE BASIS OF TURKISH WRITTEN MONUMENT - Maxmudova Dilshoda Kurbonbayevna (Galaxy International Interdisciplinary Research Journal, 2022)
Three articles on Turkic languages, history of Uzbek language, the oldest written monuments of Turkic language, the period of modern Turkish written literary language, the most reliable source for studying the history of language written monuments and modern Turkic languages and manual We are talking about dialects.